Sence of Agency: Concept, Structure, Assessment - Kulyapina, Alena M.; Fam, Anna H.; Zolotareva, Alena A. (Voprosy obrazovaniâ, 2024)
In recent years, the sense of agency has been the subject of interest for researchers in psychology, economics, sociology, political science, and education. To psychologically measure this phenomenon, Adam Tapal and his colleagues developed and validated the Sense of Agency Scale (SoAS). The aim of this study was to adapt the Russian version of the SoAS. The participants were 224 volunteers recruited through the online services.. Besides the Russian SoAS, all respondents completed instruments measuring general self-efficacy, locus of control, and belief in freedom/determinism. To analyze the psychometric properties of the Russian SoAS, methods of descriptive statistics, correlational and confirmatory factor analyses, and ω-MacDonald coefficients were used. The Russian SoAS has a clear two-factor structure, is reliable (ω = 0,81 for the sense of positive agency scale and ω = 0,87 for the sense negative agency scale), and is valid (due to theoretically substantiated relationships between the SoAS scores and the scores of general self-efficacy, locus of control, and belief in freedom/determinism). The adapted scale is reliable and valid, and can be recommended for scientific research and psychodiagnostic surveys of Russian-speaking respondents.